POLÍTICAS PÚBLICAS PARA A PROMOÇÃO DA LEITURA LITERÁRIA NA EDUCAÇÃO DO CAMPO: PRINCÍPIOS, PROGRAMAS E MATERIALIZAÇÃO - SOUZA, ELISANGELA RODRIGUES DE (2019)
Many different departments of civil organization foments actions claiming public policy to improve the conditions of instruction and to support the reading on the countryside schools. One of the political pedagogical principles these organizations assumed is that school presents a specificity, which must be worked and prioritize in otherwise of macro policy, whose put aside this particular reality. Our purpose is to understand how the countryside schools relate the policy dimension with the esthetic dimension, in order of generation of the students through the teaching of literature. We analyzed the propagation of literature in two schools, which are conceive the methodological theory orientation of countryside education, waged by the social movements. We question ourselves: how does the materialization of the public policy of literature are characterized, promoted by the government, on two countryside schools of the Paraná midwest region? What conceptions of literature surround the programs, projects and the instruction of the reading in these schools? The value of research consist to understand the possibilities of countryside schools appropriate the programs, articulating in a formative proposal. We considerate the theorists of literature instruction about the esthetic formation promoted by that lesson, in according of the policy formation idealized to the countryside schools. We base our analysis of countryside education, on the perspective of Omnilateral formation (FRIGOTTO, 2012) and reading practices, whose encourage the access of elaborated esthetical universe (CANDIDO, s/d), contributing to policy awareness of subjects (SILVA, 1988), by the instruction based on the social practice of reading (BAKHTIN, 2006). Methodologically, we analyzed the guidelines of countryside education (2002, 2006, 2010); curricular guidelines of the portuguese language (2008); development programs of literature and countryside education; and political pedagogical projects. Over the empirical analysis, we search to understand how the schools conceive the public policy, and how relates the reading practice with the conceiving of Omnilateral formation, that is, the way by this act is conducted on the school context to observe the process of policy formation and esthetic of subject through the literature, analyzing two partial cases on the public countryside schools of midwest Paraná, checking the habit of reading on the students and the pedagogical practices about the literary reading. We verify a growing development of public policy in literature field, contradicting the concrete reality of public countryside schools ordinary students observed here, like this, the development programs of reading are incipient to the literature learning to understand the policy dimension and esthetic, turned to detection of local cultural wealth, even with the efforts of schools to overcome the limits of governmental actions, which assume in their curriculum the propose to formation of rural education and social practices of reading and writing, this principles are dispersed on the praxis, and by lack of material resources and proper training, are at risk of empty the esthetic formation over the content formation.